A Comprehensive Biophysical Model of Ion and Water Transport in Plant Roots. II. Clarifying the Roles of SOS1 in the Salt-Stress Response in Arabidopsis - Foster, Kylie J.; Miklavcic, Stanley J. (Frontiers in Plant Science, 2019)
SOS1 transporters play an essential role in plant salt tolerance. Although SOS1 is known to encode a plasma membrane Na$^+$/H$^+$ antiporter, the transport mechanisms by which these transporters contribute to salt tolerance at the level of the whole root are unclear. Gene expression and flux measurements have provided conflicting evidence for the location of SOS1 transporter activity, making it difficult to determine their function. Whether SOS1 transporters load or unload Na$^+$ from the root xylem transpiration stream is also disputed. To address these areas of contention, we applied a mathematical model to answer the question: what is the function of SOS1 transporters in salt-stressed Arabisopsis roots? We used our biophysical model of ion and water transport in a salt-stressed root to simulate a wide range of SOS1 transporter locations in a model Arabidopsis root, providing a level of detail that cannot currently be achieved by experimentation. We compared our simulations with available experimental data to find reasonable parameters for the model and to determine likely locations of SOS1 transporter activity. We found that SOS1 transporters are likely to be operating in at least one tissue of the outer mature root, in the mature stele, and in the epidermis of the root apex. SOS1 transporter activity in the mature outer root cells is essential to maintain low cytosolic Na$^+$ levels in the root and also restricts the uptake of Na$^+$ to the shoot. SOS1 transporters in the stele actively load Na$^+$ into the xylem transpiration stream, enhancing the transport of Na$^+$ and water to the shoot. SOS1 transporters acting in the apex restrict cytosolic Na$^+$ concentrations in the apex, but are unable to maintain low cytosolic Na$^+$ levels in the mature root. Our findings suggest that targeted, tissue specific, overexpression or knockout of SOS1 may lead to greater salt tolerance than has been achieved with constitutive gene changes. Tissue-specific changes to the expression of SOS1 could be used to identify the appropriate balance between limiting Na$^+$ uptake to the shoot while maintaining water uptake, potentially leading to enhancements in salt tolerance.